Media Endorsements of New Product Announcements: A New Marketing Strategy. (29th December 2014) - Doukas, Angelos J.; Guo, Jie (Michael); Lam, Herbert Y. T.; Xiao, Sarah (Hong)
Abstract: This paper examines whether investors' decisions are influenced by the word content of newspaper reports of new product announcements. Using textual analysis we find that announcements of new products covered by financial newspapers with positive word content earn significant abnormal returns. These returns are 270 basis points higher than new products without positive word coverage, and such announcements bring negative impact to their rival firms' value. Our results suggest that the market reacts to the linguistic content of the new product announcement rather than to the announcement itself.